Investigation of the effect of movement and irrigation systems on temperature in the conventional drilling of cortical bone - Alexandre Gehrke, Sergio; Neto, Henrique Loffredo [UNESP]; Mardegan, Fabio E. C. [UNESP] (Churchill Livingstone, 2013)
We have compared the results of the external irrigation technique with those of a double irrigation technique with continuous intermittent movement. Maximum thermal measurements were made in the cortical part of 10 samples of bovine ribs during osteotomy to simulate the preparation of a surgical bed for the installation of dental implants at a depth of 10 mm Twenty specimens were drilled for each group: external irrigation and continuous movement (control group 1, CG1); external irrigation and intermittent movement (control group 2, CG2); double irrigation and continuous movement (test group 1, TG1); and double irrigation and intermittent movement (test group 2, TG2). The double irrigation technique gave significantly better results regardless of the drilling movement used. Thermal increases between samples was 19.2% in group CG1, 10.4% in CG2, 5.4% in TG1, and 3.4% in TG2. The double irrigation technique produced a significantly smaller increase in temperature in the cortical bone during both types of drilling (p = 0.001), which illustrated its greater efficiency compared with that of the external irrigation technique. (C) 2013 The British Association of Oral and Maxillofacial Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: Osteotomy; Bone surgery; Thermocouple; Dental implants; Irrigation